A new record of Holothuria arguinensis colonizing the Mediterranean Sea - González-Wangüemert, Mercedes (2017)
Holothuria arguinensis is reported for the first time on the south-eastern Spanish coast. One specimen of this species was identified in El Mojo´n (Alicante, Spain, 37850′54.17′′N 0845′39.90′′W). This finding widens the geographical range of H. arguinensis and demonstrates that its environmental requirements are changing. Future genetic studies in this species would allow us to improve our understanding of its colonization from the Atlantic Ocean to the Mediterranean Sea.